Changes in Internal Cerebral Vein Pulsation and Intraventricular Hemorrhage in Extremely Preterm Infants - Tanaka, Kenichi; Matsumoto, Shirou; Minamitani, Youhei; Imamura, Hiroko; Yoshimatsu, Hidetaka; Nakamura, Tomomi; Naramura, Tetsuo; Iwai, Masanori; Mitsubuchi, Hiroshi; Nakamura, Kimitoshi (American Journal of Perinatology, 2022)
Objectives This study aimed to investigate the relationship between internal cerebral vein (ICV) pulsation and intraventricular hemorrhage (IVH) and to identify the cut-off values that predict IVH. We hypothesized that the severity of ICV flow pulsations was related to IVH severity.Study Design In this prospective observational study, ICV flow was measured in 61 extremely preterm infants using ultrasonography at every 12 hours until 96 hours after birth and on days 7, 14, and 28. The ICV pulsation index (ICVPI = minimum/maximum ICV speed) was calculated and compared among the groups determined by Papile's IVH classification. The ICVPI cut-off values for IVH were determined by receiver operating characteristic curve analysis.Results Compared with those in the no IVH (NIVH) group (n = 51), the ICVPI median values in the severe IVH (SIVH; grades 3 and 4) group (n = 5) were lower at 25 to 96 hours and on day 7, whereas those in the mild IVH (MIVH; grades 1 and 2) group (n = 5) were lower at 37 to 60 hours. All SIVH events were initially detected within 60 hours after birth. The ICVPI cut-off values for SIVH were 0.92 at 13 to 24 hours, 0.42 at 25 to 36 hours, 0.58 at 37 to 48 hours, and 0.55 at 49 to 60 hours. Infants whose ICVPI values were below the cut-off value ≥3 times between 13 and 60 hours had a significantly higher SIVH incidence than those whose ICVPI values were below the cut-off value ≤2 times (57.1 vs. 1.9%, p < 0.001).Conclusion Our results indicate that SIVH had sustained pronounced internal cerebral vein pulsations and that the ICVPI values may help predict SIVH. Further research on strategies to decrease venous pressure for IVH prevention is needed.Key Points
Keywords: intraventricular hemorrhage; internal cerebral vein pulsation; infants; postnatal circulatory adaptation